Gadget Use Duration and Macro Nutrition Intake With Nutritional Status on Students of SMPN 16 Makassar - Nurul Asyifah; Aswita Amir; Sitti Sahariah Rowa; Manjilala Manjilala (Saintify Publish, 2023)
People in urban areas tend to carry out their daily activities with gadgets. excessive use of gadgets in adolescents related to nutritional status, namely high screen-time, low levels of physical activity, and makes eating patterns less suitable so that they can affect nutritional status in the long term. This type of research is observational using a cross sectional study design. The population of class VIII students of SMPN 16 Makassar is 162 people. The sample size is 116 people. The duration of using the gadget was obtained through a questionnaire, the intake of macronutrients was obtained through a 2x24 hour recall and nutritional status was obtained from anthropometric measurements. Statistical test with the Chi Square test using the SPSS program. Data is presented in the form of frequency distribution tables and narratives. The results showed that the duration of using the sample gadgets was 47.4% sufficient and 52.6% more. The sample protein intake was 31.9% sufficient and 68.1% insufficient. The sample fat intake was 44% sufficient and 56% insufficient. The sample carbohydrate intake was 29.3% sufficient and 70.7% insufficient. The nutritional status of the samples was 13.8% over nutrition, 77.6% normal nutrition and 8.6% undernutrition. Statistical test results between the variable duration of gadget use and protein intake, carbohydrate intake and nutritional status showed (P > 0.005) so there was no relationship. Meanwhile, the statistical test results between the variable duration of gadget use and fat intake (P < 0.005) so that there is a relationship between the duration of gadget use and fat intake. It is recommended to maintain a healthy diet and lifestyle, especially reducing the duration of using gadgets and increasing intake of macronutrients in order to achieve adequate consumption levels